Feasibility Study on Joining Dissimilar Aluminum Alloys AA6061 and AA7075 by Tungsten Inert Gas (TIG) - M., Ishak; Nur Fakhriah, Mohd Noordin; L. H., Shah (Penerbit Universiti Teknologi Malaysia, 2015)
The aim of this paper is to study the feasibility of welding dissimilar aluminum alloys AA6061 and AA7075 using different types of filler metals which are ER4043 and ER5356. The tungsten inert gas (TIG) welding method was used to butt joint these alloys. The effect of ER4043 (Si-rich) and ER5356 (Mg-rich) on weldability of the joint were studied through visual appearance, microstructures and hardness. It was found that, welding using filler ER5356 produced deeper penetration compared to filler ER4043. The depth of penetration obtained using filler ER5356 was 1.74 mm, while only 0.9 mm of penetration was obtained using ER4043. Microstructures at different zones of dissimilar TIG joints such as the fusion zone (FZ), the partially melted zone (PMZ) and the heat affected zone (HAZ) were identified. The grain size at FZ from filler ER5356 samples was finer compared to filler ER4043 which was 11.4 µm and 19.5 µm, respectively. The average hardness welding value of filler ER5356 samples was higher compared to filler ER4043 samples, which were 100HV and 86HV, respectively at HAZ of AA 6061, 110HV and 88HV, respectively at FZ, while 113HV and 85HV, respectively at HAZ of AA 7075. It can be concluded that TIG welding using the ER5356 filler yields better joint compared to ER4043.